INCREASING LEARNING ACTIVITIES AND OUTCOMES THROUGH COOPERATIVE LEARNING TYPE OF LISTENING TEAM WITH AUDIOVISUAL MEDIA IN STUDENTS OF SDN DUKUHSETI 01 - EPRILIANI, WIDYA AYU (Literasi, 2021)
Widya Ayu Epriliani, Aryo Andri Nugroho, Tri SugiyonoSDN Dukuhseti 01email: widyaayuepriliani1@gmail.comBased on the results of observations at SDN Dukuhseti 01, several problems were found in learning in class III which resulted in low student learning outcomes. Among them, as many as 60% of the 20 students have low activity, students pay less attention to teachers, less use of learning media, and 70% of learning outcomes have not reached the KKM. To improve the activities and learning outcomes of class III students, the researchers applied the Listening Team Cooperative Learning learning model with audiovisual media. This type of research is classroom action research through the Cooperative Learning model of Listening Team Type with Audiovisual media which consists of three cycles. Data collection techniques using tests and non-tests. Data analysis used quantitative and qualitative descriptive analysis. The results showed that the activity of students in the first cycle had an average score of 3.76 in the good category, in the second cycle the average was 4.04 in the good category and in the third cycle the average score was 4.5 in the very good category. The average student learning outcomes in the first cycle is 62, the second cycle is 70.5, and the third cycle is 87.5. The percentage of classical completeness in the first cycle was 50%, increased in the second cycle to 65%, and in the third cycle it became 100%. The conclusion of the learning outcomes shows that the cooperative learning model of Listening Team Type with audiovisual media can improve the activities and learning outcomes of students. Keywords: Cooperative Learning, Listening Team, Audiovisual